Building A Professionalism A Lecturer Strengthening The Competitiveness of The Nation - Novika, Putri Wahyu (ADI Journal on Recent Innovation, 2021)
Lecturers are one important component in the education system at universities high. The roles, tasks and responsibilities of lecturers are very meaningful to produce resources quality strength. Lecturers are required to be able to show good performance. Performance the good must be supported by competence and also professionalism. However lecturer professionalism is not always directly proportional to work professionalism. Many show that lecturers do not have professional skills. Quality professional lecturers are still low. As is known the level of professionalism lecturers are generally not optimal, this is largely influenced by factors background, including the role of government, university conditions and various other external conditions that directly or indirectly affect towards lecturer professionalism.